(untitled) (Research, Society and Development, 2022)
The SWOT Matrix proposes to the company a clear and objective view of what are its strengths and weaknesses in the internal environment, and its opportunities and threats in the external environment. This work reflects on the SWOT Matrix and Porter’s five forces as strategic tools. The objective of this study is to elaborate a strategic plan for a startup company specialized in irregular settlements regularization, adopting information technology as a strategic differential. Hence, the work was carried out from the case study of Titular Smart Regularization Company, analyzing the different ways of using these tools to obtain a highlight in the company’s segment. Thus, with this analysis, it was possible to develop strategies to obtain a favorable market position and a better organizational performance. This document also identified and described the action mode of Porter’s five competitive forces and how they influence the definition of business competitive strategy.